Aerosolized plus intravenous colistin vs intravenous colistin alone for the treatment of nosocomial pneumonia due to multidrug-resistant Gram-negative bacteria: A retrospective cohort study. (July 2021) - Almangour, Thamer A.; Alruwaili, Alya; Almutairi, Rehab; Alrasheed, Aljwhara; Alhifany, Abdullah A.; Eljaaly, Khalid; Alkofide, Hadeel; Alhammad, Abdullah M.; Ghonem, Leen; Alsharidi, Aynaa
Highlights: The rate of pneumonia due to drug-resistant Gram-negative bacteria has been growing. Colistin administered via inhalation improves lung penetration and minimizes systemic exposure. Aerosolized plus intravenous colistin was compared with intravenous colistin alone. Aerosolized colistin improved the clinical and microbiological outcomes. No statistically significant differences were found in mortality or nephrotoxicity. Abstract: Objective: To compare the effectiveness and safety of aerosolized (AER) plus intravenous (IV) colistin with IV colistin alone in patients with nosocomial pneumonia (NP) due to multidrug-resistant (MDR) Gram-negative bacteria. Methods: This was a retrospective cohort study of adults with NP who received IV colistin alone or in combination with AER colistin. The primary endpoint was clinical cure at end of therapy. Secondary endpoints included microbiological eradication, in-hospital mortality and nephrotoxicity. Results: In total, 135 patients were included in this study: 65 patients received AER plus IV colistin and 70 patients received IV colistin alone. Baseline characteristics were similar between the two groups. Clinical cure was achieved in 42 (65%) patients who received AER plus IV colistin and 26 (37%) patients who received IV colistin alone ( P = 0.01). Among a total of 88 patients who were microbiologically evaluable, 27 (42%) patients who received AER plus IV colistin and 12 (17%) patients who received IV colistin alone attained favourable microbiological outcomes ( P = 0.022). In-hospital mortality (43% vs 59%, P = 0.072) was higher in patients who received IV colistin alone, but the difference was not significant. Renal injury occurred in 31% of patients who received AER plus IV colistin and in 41% of patients who received IV colistin alone ( P = 0.198). Conclusion: AER colistin can be considered as salvage therapy as an adjunct to IV administration for the treatment of patients with NP due to MDR Gram-negative pathogens.